Dadin-Kowa Irrigation Project: A Catalyst for Rural Development in Gombe State - Salihu, Ibrahim; Saleh , Zahraddeen Mallam; Bako, Naamadu Anas (Kashere Journal of Politics and International Relations, 2023)
States increasingly seek to optimize the utilization of scarce water resources as a catalyst for rural development. Successive governments in Nigeria have been laying greater emphasis on irrigation projects as a means of improving food production, and rural livelihoods. This paper examined the contribution of Dadin-Kowa Irrigation Project on rural development in Gombe State (2015-2023). The paper uses a mixed method approach where both structured questionnaires and in-depth interviews were employed in collecting data. A representative sample of 381 respondents was proportionally selected from the three wards surrounding the irrigation project and questionnaires were administered randomly in each ward. Key relevant officials such as the Chairman of the Water Users Association, the Sectional Head of the Irrigation Project, the Gombe State Chief Produce Officer, the Chairman of Gombe State Primary Healthcare Development Agency were interviewed and the official records of the Upper Benue River Basin Development Authority, Dadin-Kowa area office and that of Gombe state Ministry of Education was used to supplement the quantitative data. The paper found that Dadin-Kowa Irrigation Project has made contribution to rural development as it substantially improved food production and the livelihood of the rural dwellers in the area. This was further corroborated by the result of the paired sample t-test which reported the significant contribution of the Project on rural development after 2015 with a mean difference of 0.4972 on food production and 0.8278 on rural livelihood respectively.